2020
DOI: 10.3390/insects11120827
|View full text |Cite
|
Sign up to set email alerts
|

Self-Selection of Agricultural By-Products and Food Ingredients by Tenebrio molitor (Coleoptera: Tenebrionidae) and Impact on Food Utilization and Nutrient Intake

Abstract: Nutrient self-selection was used to determine optimal intake ratios of macro-nutrients by Tenebrio molitor L. larvae. Self-selection experiments consisted of 9 combinations (treatments) of 8 ingredients, from a total of 20 choices, radially distributed in a multiple-choice arena presented to groups of 100 T. molitor larvae (12th–13th instar). Larvae freely selected and feed on the pelletized ingredients for a period of 21 days at 27 °C, 75% RH, and dark conditions. Consumption (g) of each ingredient, larval li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 38 publications
8
28
0
Order By: Relevance
“…However, in the study by Zhang et al [ 34 ], no clear correlation between the nutritional composition of substrates and yellow mealworm was observed. Morales-Ramos et al [ 43 ] observed in their study that a macronutrient ratio of 0.23 protein: 0.06 lipid: 0.71 carbohydrate was optimal for growth of yellow mealworm, and the intake of carbohydrates was seen to increase the efficiency of growth, whereas the intake of neutral detergent fiber had a negative impact on growth.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the study by Zhang et al [ 34 ], no clear correlation between the nutritional composition of substrates and yellow mealworm was observed. Morales-Ramos et al [ 43 ] observed in their study that a macronutrient ratio of 0.23 protein: 0.06 lipid: 0.71 carbohydrate was optimal for growth of yellow mealworm, and the intake of carbohydrates was seen to increase the efficiency of growth, whereas the intake of neutral detergent fiber had a negative impact on growth.…”
Section: Discussionmentioning
confidence: 99%
“…Both species are approved as aquafeed ingredient in EU [ 12 ], whereas T. molitor was the first insect species to acquire an EU-wide approval for human consumption [ 13 ]. The upcycling and bioconversion of several organic side-streams and wastes by T. molitor has been studied by several studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. For instance, an olive pomace-enriched substrate up to 25% enrichment sufficiently supported T. molitor larval growth, providing a means for exploitation, as well as management, of the olive processing byproducts [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The FCR (8.2) and efficiency of conversion of ingested feed (ECI) (12.2%) were as earlier reported 17 . Low feed consumption affects growth rate which in turn affects feed conversion to biomass 65 . Interestingly, cell-fed mealworms showed a higher protein and lower lipid content than wheat bran-fed mealworms, due to the higher protein content of C. necator H16.…”
Section: Discussionmentioning
confidence: 99%